2018
DOI: 10.1186/s13075-018-1540-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypogalactosylation of immunoglobulin G in rheumatoid arthritis: relationship to HLA-DRB1 shared epitope, anticitrullinated protein antibodies, rheumatoid factor, and correlation with inflammatory activity

Abstract: BackgroundGalactosylation of immunoglobulin G (IgG) is reduced in rheumatoid arthritis (RA) and assumed to correlate with inflammation and altered humoral immunity. IgG hypogalactosylation also increases with age. To investigate dependencies in more detail, we compared IgG hypogalactosylation between patients with RA, patients with axial spondyloarthritis (axSpA), and healthy control subjects (HC), and we studied it in RA on the background of HLA-DRB1 shared epitope (SE), anticitrullinated protein antibodies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In RA patients, levels of IgG galactosylation, bisection, and fucosylation are altered [201, 204, 208212]. In addition, defective galactosylation in the IgG-Fc glycans was observed in RA patients [204, 213, 214] and arthritic MRL-lpr/lpr mice [215]. It was found that agalactosyl IgG has significantly reduced binding to Clq and to Fc γ Rs [216].…”
Section: Igg Glycosylationmentioning
confidence: 99%
“…In RA patients, levels of IgG galactosylation, bisection, and fucosylation are altered [201, 204, 208212]. In addition, defective galactosylation in the IgG-Fc glycans was observed in RA patients [204, 213, 214] and arthritic MRL-lpr/lpr mice [215]. It was found that agalactosyl IgG has significantly reduced binding to Clq and to Fc γ Rs [216].…”
Section: Igg Glycosylationmentioning
confidence: 99%
“…SSc is an autoimmune disease causing fibrosis of the skin and internal organs. IgG, as a key component of the immune system, is involved in many autoimmune diseases. , Studying the glycosylation in different IgG subclasses may provide insights into the association of IgG glycosylation with SSc.…”
Section: Resultsmentioning
confidence: 99%
“…Glycan migration is mediated by an electric field, leading to the separation of positional glycan isomers and quantification can be achieved using labeled maltose [ 69 , 70 ]. The advantage of this technique is that it has high separation power, only requiring a small sample amount and with a quick turnaround time [ 71 ]. Glycan separation can also be performed on UPLC via hydrophilic interaction and fluorescence detection.…”
Section: Glycomics Methodologiesmentioning
confidence: 99%